Identification of Clinical Markers Associated with Cholesteatoma in Patients of Chronic Suppurative Otitis Media - Azhar, Hareem; Manzoor, Faisal; Riaz, Naeem; Haleem, Uswah; Alvie, Maheen; Farooq, Shahid (Pakistan Armed Forces Medical Journal, 2025)
ABSTRACT Objective: To assess the importance of different clinical markers in predicting the presence of cholesteatoma in patients of Chronic Suppurative Otitis Media. Study Design: Cross-sectional study. Place and Duration of Study: ENT Department, Combined Military Hospital, Rawalpindi Pakistan from Jul 2023 to Jan 2024. Methodology: Patients who presented with chronic ear discharge along with the presence of clinical markers suggestive of cholesteatoma were evaluated thoroughly with the aid of detailed examination through an otoscope and microscope. Hearing loss was evaluated by tuning fork tests and Pure Tone Audiometry. All the patients included underwent a resolution CT scan of the temporal bone and subsequent mastoid exploration to confirm the presence of cholesteatoma. Results: In totality, 80 patients were evaluated, out of which 27 were females and 53 were males. Thirty-seven had cholesteatoma, and 43 had non-specific inflammation. Out of 37 patients, 12 patients with middle ear polyp (32.5%) had cholesteatoma, 10 patients (27%) with attic perforation (retraction pocket) were diagnosed with cholesteatoma whereas 5(13.5%) with granulation tissue, 7(18.9%) with posterior-superior perforation and 3(8.1%) with non-resolving aural discharge through a central perforation had cholesteatoma as well. Conclusion: It has been concluded that aural polyps, followed by attic perforations, serve as strong clinical indicators for the presence of cholesteatoma. Recognizing these signs early is essential to make certain timely interventions, preventing long-term complications that could potentially become life-threatening.